IAA Oxidase Inhibitors from Normal and Mutant Maize Plants - Gelinas, D. (1969)
Extracts of maize (Zea mays L.) plants contain substances which, in vitro, inhibit an indoleacetic acid (IAA) oxidase enzyme from maize. The extracts can be freed of inhibitors by dialysis or by passage through columns of polyvinylpyrrolidone powder. Inhibitor-free extracts contain an IAA oxidase enzyme which requires a phenolic co-factor and is stimulated by Mn(2+). IAA oxidase inhibitor and total phenol levels were compared for normal maize and for the maize mutant Knotted (Kn). In plants up to 18 days old the level of heat stable, water soluble IAA oxidase inhibitors increases with increasing dosage of the Kn allele. Increased inhibitor content is accompanied, but not paralleled, by increased content of total phenols. Although several inhibitors are present in crude extracts, most inhibition can be attributed to 1 compound. This compound is not destroyed by horseradish peroxidase in the absence of IAA. At pH 3.5 it is not extracted into ether, but it is rendered ether-extractable by incubation in 2 n KOH for 5 hr at room temperature. This compound is tentatively identified as an ester of ferulic acid and some unknown moiety.